1996
DOI: 10.1093/jn/126.2.434
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin A Supplementation Fails to Reduce Incidence of Acute Respiratory Illness and Diarrhea in Preschool-Age Indonesian Children

Abstract: Vitamin A supplementation of populations of vitamin A-deficient preschool-age children has been shown to reduce childhood mortality, but the primary preventive effects of such supplements on childhood infectious diseases have not been carefully evaluated. We conducted an individually randomized, placebo-controlled, double-masked trial among 1,407 Indonesian preschool-age children, to measure the effects of high dose vitamin A on acute respiratory and diarrheal illnesses. Signs and symptoms of morbidity were mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
77
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(81 citation statements)
references
References 24 publications
4
77
0
Order By: Relevance
“…However, in this study population, vitamin A supplementation had little effect on morbidity rates with no change in the incidence of diarrhea, but an 8% increase in the incidence of cough episodes (Dibley et al, 1996). Since respiratory infection did not affect growth, there is no reason to relate the small increase in incidence due to vitamin A supplementation to poor growth.…”
Section: Complex Interactions With Infection and Diet H Hadi Et Almentioning
confidence: 58%
See 1 more Smart Citation
“…However, in this study population, vitamin A supplementation had little effect on morbidity rates with no change in the incidence of diarrhea, but an 8% increase in the incidence of cough episodes (Dibley et al, 1996). Since respiratory infection did not affect growth, there is no reason to relate the small increase in incidence due to vitamin A supplementation to poor growth.…”
Section: Complex Interactions With Infection and Diet H Hadi Et Almentioning
confidence: 58%
“…Details of the study design and the effect of vitamin A supplementation on infectious diseases are described elsewhere (Dibley et al, 1996), but important aspects of the trial methods are summarized below.…”
Section: Study Population and Designmentioning
confidence: 99%
“…Various studies had proved that vitamin supplementation to these children`s diet would reduce their mortality rate by almost 23%, even though the mechanism is still unknown (31). It is believed that such benefits are seen through its ability to reduce the prevalence of infectious diseases.…”
Section: Discussionmentioning
confidence: 99%
“…The second trial showed that vitamin A deficiency have made patients more susceptible to respiratory and gastrointestinal infections. The third trial in Indonesia showed that prescribing high doses of vitamin A to preschool children decreased mortality by 34% (31).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation